2013
DOI: 10.1080/1062936x.2013.773375
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Evaluation Support System (HESS) for predicting repeated dose toxicity using toxicological categories

Abstract: Repeated dose toxicity (RDT) is one of the most important hazard endpoints in the risk assessment of chemicals. However, due to the complexity of the endpoints associated with whole body assessment, it is difficult to build up a mechanistically transparent structure-activity model. The category approach, based on mechanism information, is considered to be an effective approach for data gap filling for RDT by read-across. Therefore, a library of toxicological categories was developed using experimental RDT data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 15 publications
4
59
0
Order By: Relevance
“…Comparing our study results with previous published models for LOEL endpoints, our model has shown better predictive power than studies published by De Julian-Ortiz et al [29], Mazzatorta et al [30] and Gadaleta et al [24]. The Sakuratani et al [31] study had only categorized chemicals into 33 chemical categories, while in our study we formed new categories for each of the chemicals to facilitate better prediction of their LOELs. The study performed by Mumtaz et al [32] used 234 chemicals for construction of the QSAR model, but authors did not confirm the predictive power of this model using an external test set, thus it is not possible to compare our results with this model.…”
Section: Resultssupporting
confidence: 51%
“…Comparing our study results with previous published models for LOEL endpoints, our model has shown better predictive power than studies published by De Julian-Ortiz et al [29], Mazzatorta et al [30] and Gadaleta et al [24]. The Sakuratani et al [31] study had only categorized chemicals into 33 chemical categories, while in our study we formed new categories for each of the chemicals to facilitate better prediction of their LOELs. The study performed by Mumtaz et al [32] used 234 chemicals for construction of the QSAR model, but authors did not confirm the predictive power of this model using an external test set, thus it is not possible to compare our results with this model.…”
Section: Resultssupporting
confidence: 51%
“…[10][11][16][17][18] A number of in silico profilers have been developed for a variety of organ-level toxicities, such as skin sensitisation, respiratory sensitisation, genotoxicityand hepatotoxicity. [13][14][15][19][20][21] However, very few profilers have dealt with toxicity induced by mitochondrial dysfunction. 1,22,23 This is, in part, due to the number of mechanisms by which a chemical could induce mitochondrial dysfunction 24 .…”
Section: -12mentioning
confidence: 99%
“…Several related studies have been conducted, and recently a prediction system based on categorization for repeated dose toxicity, called the Hazard Evaluation Support System (HESS), was developed in Japan. [11] In a similar manner, the approach based on cell-based assays involves conducting tests using cells instead of animals, and assessing the presence and degree of toxicity of the target substance based on these tests. The Ames test (detection of mutagenicity using bacteria), which evaluates the mutagenicity of chemical substances, is well known, and several cell-test methods are described in the guidelines of the Organisation for Economic Co-operation and Development (OECD).…”
Section: Estimation Based On Structure-activity Relationships And/or mentioning
confidence: 99%